RELASI ILMU, FILSAFAT DAN AGAMA DIMENSI PARADIGMA PROPETIK - Yudi Fahrian; Aidil Fitri (Fakultas Hukum Universitas IBA Palembang, 2022)
Abstract There are three things that become tools for humans to seek the truth, namely philosophy, science and religion. Although the purpose of these three aspects is to seek the truth, they cannot be categorized as the same thing (synonyms). In general, philosophy is considered something very free because it thinks without limits. While religion, prioritizes revelation / inspiration from substances that are considered God. Everything that comes from God, in a religious perspective is a truth that cannot be denied. While science is a set of methods to find the truth. Understanding the three aspects above is quite urgent for everyone, because everyone definitely needs an understanding of the problems faced in everyday life. How are these three aspects related? How are the three aspects related to the prophetic concept? The approach used in this paper uses a descriptive method. The conclusion of this study, between philosophy and science and religion, has a very close relationship. This is based on the third goal, namely the search for truth. There are differences and similarities in science, philosophy, and religion, namely about the truth. However, these three aspects are horizontally interconnected, but vertically, only religion has them. Religion besides having a horizontal relationship with philosophy and science, it also has a vertical relationship with God as the worshiper of man himself.